A Critique on Networks of Outrage and Hope: Social Movements in the Internet Age - Salman Sadeghizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Networks of Outrage and Hope is one of the newest explanations about new social movements. Alain Touraine adopted the “new social movements” expression to describe the new forms of societal recourse for change in “post-industrial society” and made it the counterpart for “social movements” in “industrial society”. Touraine and his students, Castells and Melucci, analyzed the mentioned movements in a completely different social context, although they were not the same in their method. Other thinkers like Offe have focused on economic relations, and Englehart and Pakulski emphasized the cultural nature of these newly apparent movements. Castells in Networks of Outrage and Hope speaks of the network society in which there are the super network of power and super network of counter-power describing new social interactions. In the network society, movements have a hybrid characteristic and are divided into two spheres of places and spaces, which in turn make a new model of actions. Castells refers to this model to analyze the movements in the age of information and reconsider the events in Iceland, Tunisia, Egypt, Syria, Spain, and the U.S. by applying the mentioned model. The merit of Castells analysis is to introduce a well-coherent theoretical framework to explain the dynamics of movement, and the demerit is omitting the logic of social relations of production and consumption in the studied societies.